PENGEMBANGAN MEDIA AUDIO VISUAL PASSING BAWAH DALAM PERMAINAN BOLA VOLI SISWA KELAS VI SD INPRES OEBA I KUPANG - Lukas M. Boleng; Veramtya M. M. Flora Babang; Ratib Suaib (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
ABSTRACT This research is research and development. The subjects in this trial were students of class VI SD Inpres Oeba 1 Kupang, small scale trials totaling 12 children and large scale trials totaling 36 children and had never received material with this audio visual media. The instruments used were questionnaires and audio visual media products. To analyze data, use descriptive statistics with a percentage. In small scale trials it was found that many 7 (58.33%) children had "very good" responses, 3 (25%) children had "good" responses, and as many as 2 (15.38%) children has a "good enough" response. Whereas in the large-scale trial the responses of students were 26 (72.22%) children stated "very good", while as many as 7 (19.44%) children stated "good" and as many as 3 (8.33% ) the child states "well enough". So it can be concluded that the development of audio-visual passing media down in the game when the volleyball of grade VI students of SD Inpres Oeba 1 Kupang is very good. So the audio visual passing media product developed by the researcher can be said to be feasible to be used in the learning process of PJOK on the material of passing volleyball under school.Keywords: Audio Visual Media, Volleyball Games, Elementary School Students